Optimalisasi Pelaporan Digital Fast Response Internal di Rumah Sakit dalam Pencegahan dan Penanganan Kekerasan untuk Melindungi Semua Pihak - Yulia Audina Sukmawan; Ifrani Ifrani; Muhammad Samir Sayyar; Noor Aulia; Daddy Fahmanadie; M. Ali Amrin; Dadang Abdullah; Eko Taufikur Rahman; Muhammad Topan; Abdul Halim Barkatullah (FKIP, Universitas Palangka Raya, 2026)
Violence against medical and health personnel remains a significant challenge in healthcare services due to its adverse effects on healthcare worker safety, service quality, and the safety culture within hospitals. The low rate of incident reporting, resulting from the absence of an accessible, secure, and integrated reporting mechanism, further limits the effectiveness of violence prevention and response efforts. This community service program aimed to strengthen the violence prevention and response system at Dr. Soeharsono Hospital, Banjarmasin, through capacity building, the development of a Standard Operating Procedure (SOP) for Violence Incident Reporting, the establishment of a Violence Prevention and Response Task Force, and the development of the Fast Response Internal digital reporting mechanism. The program was conducted on June 8, 2026, involving 30 participants consisting of hospital management representatives, medical personnel, and healthcare workers using a participatory, needs-based approach. Program evaluation was carried out using pre-test and post-test instruments, with the results analyzed descriptively. The findings demonstrated an improvement in participants' level of understanding from 49.0% in the pre-test to 95.7% in the post-test. The program also produced several governance instruments, including the organizational structure of the Violence Prevention and Response Task Force, the SOP for Violence Incident Reporting, and the Fast Response Internal digital reporting mechanism integrated with QR Codes, Google Forms, and a monitoring dashboard to support incident reporting, verification, documentation, and systematic follow-up. This program contributes to strengthening hospital governance through the development of an integrated violence prevention and response system and has the potential to be adopted by other healthcare facilities.